Evaluating the Fit of Co-management for Small-Scale Fisheries Governance in Timor-Leste - Tilley, Alexander; Hunnam, Kimberley J.; Mills, David J.; Steenbergen, Dirk J.; Govan, Hugh; Alonso-Poblacion, Enrique; Roscher, Matthew; Pereira, Mario; Rodrigues, Pedro; Amador, Teresa; Duarte, Agustinha; Gomes, Mario; et al. (Frontiers in Marine Science, 2019)
Fisheries co-management is an increasingly globalised concept, and a cornerstone of the Voluntary Guidelines for Securing Sustainable Small-scale Fisheries in the Context of Food Security and Poverty Eradication. Timor-Leste is a politically young country in the relatively rare position of having underexploited fisheries that can be leveraged to improve coastal livelihood outcomes and food security. The collaborative and decentralised characteristics of co-management appeal to policymakers in Timor-Leste with provisions for co-management and customary laws applied to resource use incorporated into state law in 2004, and again in 2012. The first fisheries co-management pilots have commenced where management arrangements have been codified through tara bandu, a process of setting local laws built around ritual practice that prohibits nominated activities under threat of spiritual and material sanctions. To date, however there has been little critical evaluation of the suitability of co-management or tara bandu in the Timor-Leste fisheries context. To address this gap, we adapt the interactive governance framework to review the ecological, social and governance characteristics of Timor-Leste’s fisheries to explore whether co-management offers a valid and viable resource governance model. We present two co-management case studies and examine how they were established, who was involved, the local institutional structures, and the fisheries governance challenges they sought to address. Despite their relative proximity, the two sites contrasted in local ecology and fishery type; community institutions were starkly different but equally strong; and one site had tangible economic benefits to justify compliance, where the other had marginal and anecdotal fishery gains. In our review of the broader governance landscape in Timor-Leste, we see co-management as a useful mechanism to govern small-scale fisheries, but there is a need to connect legitimised local institutions with hierarchical governance of higher and external influences. Initial successes with implementing tara bandu incorporating a small marine closure have stimulated other communities to implement no-take zones - one universally popular but very limited interpretation of co-management. However, we highlight the need for a set of guiding principles to ensure legitimate community engagement, and avoid external appropriation that may reinforce marginalization of certain user groups or customary power hierarchies.